Morphometric Differentiation in a Field Population of Dichroplus maculipennis (Orthoptera: Acrididae: Melanoplinae) under Outbreak and Non-Outbreak Situation - Mariottini, Yanina (2015)
Dichroplus maculipennis is one of the most damaging grasshopper species of Argentina. Individuals of this species at high density are historically known to show aggregation behavior and dispersal flights, attributes that might suggest that it does exhibit to some extent phase polyphenism in relation to population density. Phase polyphenism is a complex phenomenon and the amplitude of phase change is usually species-dependent. Morphological differences between gregarious and solitarious locusts can be measured and analyzed in order to characterize the phase status. The objective of this study was to evaluate morphometric differences between individuals of a D. maculipennis field population in the southern Pampas region of Argentina during non-outbreak and outbreak conditions including the magnitude of sexual size dimorphism related to variation in density. Collected individuals in the outbreak condition totaled 804 (422 females, 382 males) and those in non-outbreak condition were 325 (141 females, 184 males). Six morphometric characters were measured and two ratios (F/C and E/F) usually used to discriminate between solitarious and gregarious individuals in true locust species were calculated. Results show that size traits of D. maculipennis change over time at the population level, and that these changes correlate with outbreak vs non-outbreak populations. Females and males of D. maculipennis in outbreak conditions are significantly larger than in non-outbreak conditions. Furthermore, significant change over time was recorded in values of the two ratios calculated. D. maculipennis showed female biased sexual size dimorphism in both outbreak and non-outbreak conditions. There is a smaller difference in body size among females and males in outbreak conditions than in females and males in non-outbreak conditions. These results may be an indication of the presence of densitydependent phenotypic plasticity in this species, but additional experiments are required in order to establish a causal relationship between population density and changes in size traits.